Predictions of crowdfunding campaign success: The influence of first impressions on accuracy and positivity - Etienne Schraven; Elco van Burg; Marco van Gelderen; Enno Masurel (Journal of Risk and Financial Management, 2020)
Crowdfunding has quickly gained popularity in recent years, providing an additional way for entrepreneurial individuals and organizations (creators) to attract funds for their projects. Scholars have been interested in predicting the success of crowdfunding campaigns, by relating campaign characteristics to the actual success of these campaigns. We take one step back by studying the cognitive processes of the crowd. This paper uses an experimental approach to establish whether participants' predictions on the success of crowdfunding campaigns based on first impressions are as positive and as accurate as those derived from more thorough analyses. We employ a two-study replication design, in which individuals estimate the success of crowdfunding campaigns in two conditions: with limited time and with unlimited time. The results show that prediction accuracy in both conditions is equal, yet shorter time availability results in assessments that are more negative. We discuss implications for creators and for funders.
Keywords: 330; crowdfunding; prediction; accuracy; positivity